![y=-2x+3](https://img.qammunity.org/2023/formulas/mathematics/high-school/8rtcwxdfz0uecpm44ag9dzk1bxozaaklsm.png)
In the first column you have the value of x, then to find the mistake you substitute in the equation the given value of x and evaluate to findthe corresponding value of y:
When x is 1:
![\begin{gathered} y=-2(1)+3 \\ y=-2+3 \\ y=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/q7aj31b7gqwnauu6897i6bmx5998u1s0a5.png)
When x is 2:
![\begin{gathered} y=-2(2)+3 \\ y=-4+3 \\ y=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/yt8cg1qs41sge21mpg8yfptbvao9bw54wt.png)
When x is 3:
![\begin{gathered} y=-2(3)+3 \\ y=-6+3 \\ y=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/553sili4fdkrt6rotg4g8urc17wvdxb2cl.png)
When x is 4:
![\begin{gathered} y=-2(4)+3 \\ y=-8+3 \\ y=-5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ce0z0o7qxzwjo6yp9io9uf4fd1ym5howr2.png)
As you can see the incorrect value of y is when x=1, because when x is 1 y is 1 not 2 as in the given table